Acute decompensated heart failure. What has changed in the clinical guidelines in 2021? - Igor V. Zhirov; Svetlana N. Nasonova; Ulia A. Khalilova; Yulia F. Osmolovskaya; Irina A. Zhirova; Rinat R. Gimadiev; Olga Ia. Chaikovskaia; Oleg M. Reitblat; Iuliia Sh. Prints; Anatoly G. Kochetov; Sergey N. Tereshchenko (ZAO "Consilium Medicum", 2022)
In September 2021, the European Society of Cardiology issued new guidelines on the management of patients with heart failure (HF). In the current version, experts have focused on the 4 most common variants: acute HF decompensation, acute pulmonary edema, cardiogenic shock, and isolated right ventricular failure. There has been a change in approaches to the initial management of patients with acute HF decompensation towards a decrease in the evidence-based use of peripheral vasodilators and a "return" to loop diuretics as the basis of treatment. This raises the question of monitoring the efficacy of diuretic therapy. The paper presents an algorithm proposed by the European Society of Cardiology.